Evaluating the Role of Information Services in Supporting Linguistic Minorities in Education - Gopal, G. Raman; Gopal, G. Lakshmanan; Sayfiddinov, Jahongir; Chokkalingam, Vinoth Kumar; Rajendran, Megala; Ergashev, Rasulbek (Indian Journal of Information Sources and Services, 2025)
Linguistic minorities often struggle to access equitable education in increasingly multicultural and multilingual societies. This research examines the impact of information services libraries, digital platforms, language support centers, and community outreach services on the educational needs of linguistic minority students. Using surveys, case studies, interviews, and a combination of quantitative and qualitative methods with educators, students, and information professionals, this research aims to understand the contributions of such services to language skills, academic achievement, cultural integration, and digital technology usage. The findings underscore that tailored information services are essential in resolving communication barriers, meeting inclusive resource requirements, and providing social integration and a safe environment to minority learners. Yet, many learners still face barriers, including lack of funding, multilingual materials, and poorly trained service providers. This study emphasizes the gaps in policy support and strategic frameworks at the policy level to improve the effectiveness of information services in fostering a supportive educational ecosystem for all learners, regardless of language.